Notas sobre el despliegue de proclamación territorial de Knipolegus cabanisi - Vides Almonacid, Roberto (1992)
The territorial display in ten males of K. cabanisi were observed in Alnus and Podocarpus montane forests in NW Argentina. There are four stages in this display, basically more visual than auditory. A comparison with K. aterrinus display is discussed